Public relations writing - Newsom, Doug (Thomson Wadsworth, 2008)
This text guides you through a logical progression of PR writing, starting with an explanation of how this kind of writing is unique and by exploring the legal and ethical obligations. The writing principles section, which covers both style and techniques, is followed by Public Relations writing assignments that you'll likely have to do in your early jobs: emails, memos, letters, reports and proposals, backgrounders and position papers. Writing for mass media and the more complex public relations writing functions, including media kits, media pitches, print and online newsletters, brochures, magazines, including those online, and annual reports are also covered in this comprehensive guide